Fish Feeder And Monitoring Temperature Control System Menggunakan Metode Protoype pada Akuarium Ikan Hias Koki Berbasis Internet Of Things - AB Susanto; Sindu Arianto; Joko Purnomo; Sulistiyasni . (STMIK IKMI Cirebon, 2021)
IoT in this research serves to integrate and connect all electronic devices using the internet network. This system will make it easier for users to feed fish from a distance and get information about the state of water.Arduino utilizes the ATMega microprocessor to control a variety of sensors. For example, to monitor the condition of a room and make it possible to